One point fixation of zygomatic tripod fractures in the zygomatic buttress through Keen's intraoral approach: A review of 30 cases - Abu Dakir; T Muthumani; N P Prabu; Rakesh Mohan; Abhishek Maity (Wolters Kluwer Medknow Publications, 2015)
For decades, facial beauty and esthetics have been one of the most important quests of the human race. The lateral prominence and convexity of the zygomatic bone makes it the most important bone for providing the aesthetic facial look and sets up the facial width but at the same time this prominence and convexity makes this bone more vulnerable to injury. Zygomatic complex fractures or tripod fractures are the second most common fractures after nasal fractures among facial injuries. Several studies have been undertaken regarding the reduction and fixation of zygomatic fractures with mini plates and screws. In 2002 Fujioka et al in vivo studies successfully proved that one point fixation at the zygomaticomaxillary complex gives three point alignment and sufficient rigidity when the fractures are not comminuted. In this article, 30 cases have been reviewed with one point fixation of zygomatic complex tripod fractures at the zygomatic buttress through Keen's intraoral approach along with advantages and disadvantages.